Batteries : Materials Principles and Characterization Methods - Liao, Zhen (IOP Publishing Ltd, 2021)
This research and reference text provides an introduction to battery fundamentals, exploring some of the state-of-the-art characterisation methods currently employed by the energy storage community. Covering the essential electrochemistry, impedance spectroscopy, solid state chemistry, electrochemical engineering, materials sciences and in-situ characterization methods for batteries, the text acquaints non-battery researchers with the field, and provides a comprehensive reference for specialists in sub-fields of battery research.
Keywords: Electric batteries.; elektronické knihy; electronic books